2003
DOI: 10.1007/s00236-003-0118-7
|View full text |Cite
|
Sign up to set email alerts
|

Sticky-free and overhang-free DNA languages

Abstract: Abstract. An essential step of any DNA computation is encoding the input data on single or double DNA strands. Due to the biochemical properties of DNA, complementary single strands can bind to one another forming double-stranded DNA. Consequently, data-encoding DNA strands can sometimes interact in undesirable ways when used in computations. It is crucial thus to analyze properties that guard against such phenomena and study sets of sequences that ensure that no unwanted bindings occur during any computation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 21 publications
0
39
0
Order By: Relevance
“…It can be shown that also Lev d,k is a similarity relation, with parameters (d, d + k) -see [17]. We note that for most of the DNA language properties considered in [9,15,16] the above problem is undecidable for context-free languages. As the (θ, sim)-bond-free property seems to be rather general, it might be surprising that the same problem is decidable.…”
Section: Definition 1 a Binary Relation Sim Is Called A Similarity Rmentioning
confidence: 89%
“…It can be shown that also Lev d,k is a similarity relation, with parameters (d, d + k) -see [17]. We note that for most of the DNA language properties considered in [9,15,16] the above problem is undecidable for context-free languages. As the (θ, sim)-bond-free property seems to be rather general, it might be surprising that the same problem is decidable.…”
Section: Definition 1 a Binary Relation Sim Is Called A Similarity Rmentioning
confidence: 89%
“…1 (a), and intermolecular, (b) and (c). The following properties of a DNA language L ⊆ Σ + preventing such a hybridization have been defined in [4,8,10].…”
Section: Undesirable Bonds In Dna Languagesmentioning
confidence: 99%
“…Solid languages are also used in [10] as a tool for constructing error-detecting DNA languages that are invariant under bio-operations. We refer to [6,10,11] for further examples and for mutual relations between classes of a DNA languages satisfying these properties.…”
Section: Undesirable Bonds In Dna Languagesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in vitro biomolecular computing often considers them as disadvantages because it is very likely that the secondary structure formation of a DNA/RNA strand will prevent it from interacting with other DNA/RNA strands in the expected, pre-programmed way. Thence, many studies exist on how to free sequence sets from secondary structures [4], [5], [6], [7], [8], [9], [10].…”
Section: Introductionmentioning
confidence: 99%